Effect of pollination modes on yield components in Indian mustard (Brassica juncea L.) - Kanika Nagpal; Sunita Yadav; Yogesh Kumar; Robin Singh (Journal of Oilseed Brassica, 2026)
Effect of different modes of pollination on yield parameters of Indian mustard showed that the maximumnumber of pods/plant, pod length, pod setting (%), number of seeds/pod, thousand seed weight, seed yield/plot, seed germination (%), seed vigour and oil content (508.72 pods/plant, 5.69 cm, 86.32%, 15.66 seeds/pod,6.87 g, 17.63 q/ha, 89.20%, 628.12 and 39.42%, respectively) were in open pollination followed by that in beepollination (404.56 pods/plant, 4.92 cm, 78.33%, 14.26 seeds/pod, 6.39 g, 15.57 q/ha, 85.20%, 542.54 and38.36%, respectively) and pollinators’ exclusion (287.56 pods/plant, 3.89 cm, 65.87%, 12.24 seeds/pod, 5.30g, 13.01 q/ha, 78.40%, 385.54 and 37.04%, respectively). Seed yield increased by 35.50 and 19.66 per cent inopen pollinated and Apis mellifera pollinated plots, respectively as compared to pollinators’ exclusion.